Interval-censored survival analysis of mild traumatic brain injury with outcome based neuroimaging clinical applications. (August 2020) - Vanier, Cheryl; Pandey, Trisha; Parikh, Shaunaq; Rodriguez, Alan; Knoblauch, Thomas; Peralta, John; Hertzler, Amanda; Ma, Leon; Nam, Ruslan; Musallam, Sami; Taylor, Hallie; Vickery, Taylor; et al.
Objective: The purpose of this study was to assess the relationship between MRI findings and clinical presentation and outcomes in patients following mild traumatic brain injury (mTBI). We hypothesize that imaging findings other than hemorrhages and contusions may be used to predict symptom presentation and longevity following mTBI. Methods: Patients (n = 250) diagnosed with mTBI and in litigation for brain injury underwent 3T magnetic resonance imaging (MRI). A retrospective chart review was performed to assess symptom presentation and improvement/resolution. To account for variable times of clinical presentation, nonuniform follow-up, and uncertainty in the dates of symptom resolution, a right censored, interval censored statistical analysis was performed. Incidence and resolution of headache, balance, cognitive deficit, fatigue, anxiety, depression, and emotional lability were compared among patients. Image findings analyzed included white matter hyperintensities (WMH), Diffusion Tensor Imaging (DTI) fractional anisotropy (FA) values, MR perfusion, auditory functional MRI (fMRI) activation, hippocampal atrophy (HA) and hippocampal asymmetry as defined by NeuroQuant ® volumetric software. Results: Patients who reported LOC were significantly more likely to present with balance problems (p < 0.001), cognitive deficits (p = 0.010), fatigue (p = 0.025), depression (p = 0.002), and emotional lability (p = 0.002). Patients with LOC also demonstrated significantly slower recovery of cognitive function than those who did not lose consciousness (p = 0.044). Patients over the age of 40 had significantly higher odds of presenting with balance problems (p = 0.006). Additionally, these older patients were slower to recover cognitive function (p = 0.001) and less likely to experience improvement of headaches (p = 0.007). Abnormal MRI did not correlate significantly with symptom presentation, but was a strong indicator of symptom progression, with slower recovery of balance (p = 0.009) and cognitive deficits (p < 0.001). Conclusion: This analysis demonstrates the utility of clinical data analysis using interval-censored survival statistical technique in head trauma patients. Strong statistical associations between neuroimaging findings and aggregate clinical outcomes were identified in patients with mTBI.